Soft piezoresistive sensors for integration into smart wearables - Tama, Derya (2019)
By the recent advances in intelligent textile applications, textile sensors have gained an important role and the interest in developing new sensor solutions has increased. Therefore, this study focused on developing new flexible pressure sensors based on piezoresistive materials, using different materials as electrodes, as well as different methods for joining the material layers. Within this context, Linqstat film and conductive silicone were taken as piezoresistive material. A silver-plated polyamide fabric, two kinds of conductive inks, aluminium foil and the conductive silicone were used as electrodes. To join the layers, ultrasonic welding, hot press and an oven were used as equipment. Although some samples failed to work as sensors, most of the sensors exhibited good performance.